Back Cover: Total Synthesis, Stereochemical Assignment, and Field‐Testing of the Sex Pheromone of the Strepsipteran Xenos peckii (Chem. Eur. J. 18/2016). Issue 18 (23rd March 2016) - Zhai, Huimin; Hrabar, Michael; Gries, Regine; Gries, Gerhard; Britton, Robert
Abstract : The female of the parasitic insect Xenos peckii develops inside paper wasps. Even as an adult, she remains grub‐like. Protruding only her cephalothorax between abdominal sclerites of her highly mobile host wasp, she releases a potent sex pheromone, (3 R, 5 S, 9 R, 7 E, 11 E )‐3, 5, 9, 11‐tetramethyl‐7, 11‐tridecadienal, that attracts a winged but extremely short‐lived (four hour) male (Photos: Michael Hrabar; design: Stephen DeMuth). More information can be found in the Communication by R. Britton et al. onpage 6190 ff.